2019
DOI: 10.3390/ijms20163883
|View full text |Cite
|
Sign up to set email alerts
|

GRP94 Is Involved in the Lipid Phenotype of Brain Metastatic Cells

Abstract: Metabolic adaptation may happen in response to the pressure exerted by the microenvironment and is a key step in survival of metastatic cells. Brain metastasis occurs as a consequence of the systemic dissemination of tumor cells, a fact that correlates with poor prognosis and high morbidity due to the difficulty in identifying biomarkers that allow a more targeted therapy. Previously, we performed transcriptomic analysis of human breast cancer patient samples and evaluated the differential expression of genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Interestingly, brain-tropic breast cancer lines exhibit reprogrammed lipid metabolism, including altered lipid transport, synthesis, and beta-oxidation [48][49][50] , which may reflect the fact that some breast cancers can use different strategies to overcome the limited access to lipids in the brain. The finding that FASN expression was high in all human breast cancer brain metastases examined argues that a requirement for de novo synthesis may be a common way to overcome lipid limitation in this tissue; however, whether activation of fatty acid synthesis is important prior to seeding the brain, or is induced by the lipid-poor brain tissue microenvironment remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, brain-tropic breast cancer lines exhibit reprogrammed lipid metabolism, including altered lipid transport, synthesis, and beta-oxidation [48][49][50] , which may reflect the fact that some breast cancers can use different strategies to overcome the limited access to lipids in the brain. The finding that FASN expression was high in all human breast cancer brain metastases examined argues that a requirement for de novo synthesis may be a common way to overcome lipid limitation in this tissue; however, whether activation of fatty acid synthesis is important prior to seeding the brain, or is induced by the lipid-poor brain tissue microenvironment remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Organotropic gene expression, gene signatures, and metabolic advantages are shown that mediate BC metastasis to the brain 82 - 84 , 132 , 136 , 163 . Autophagy-mediated metabolic adaptation, interaction with astrocytes, and mediator signaling 109 , 132 , 136 , 138 , 163 , 164 are also proposed to modify cancer cells, which are able to establish and grow in the brain environment.…”
Section: Figurementioning
confidence: 99%
“…The HSP90B1 overexpression observed in the brain metastatic breast cancer cell line was accompanied by upregulation of anti‐apoptotic genes such as B‐cell lymphoma 2 ( BCL‐2 ), cellular inhibitor of apoptosis protein ( HIAP1 ), and X‐linked inhibitor of apoptosis protein ( XIAP ), facilitating the survival of metastasized cells. In addition, activation of pro‐survival autophagy due to HSP90B1 upregulation was also observed in the brain metastatic cells, and the ablation of HSP90B1 reduced the viability of brain metastatic cells in vitro as well as brain metastasis in vivo, increasing the survival of the animals compared with the control groups 46,47 . The overexpression of HSP90B1 among breast cancer stem cells in CD44 hi /CD24 lo phenotype and in oxidative‐stress‐resistant breast cancer cells contributing toward enhanced proliferation and migration further strengthens the importance of HSP90B1 in highly aggressive breast cancer cells as a potential therapeutic target 48,49 .…”
Section: Discussionmentioning
confidence: 68%
“…In addition, activation of pro-survival autophagy due to HSP90B1 upregulation was also observed in the brain metastatic cells, and the ablation of HSP90B1 reduced the viability of brain metastatic cells in vitro as well as brain metastasis in vivo, increasing the survival of the animals compared with the control groups. 46,47 The overexpression of HSP90B1 among breast cancer stem cells in CD44 hi /CD24 lo phenotype and in oxidative-stress-resistant breast cancer cells contributing toward enhanced proliferation and migration further strengthens the importance of HSP90B1 in highly aggressive breast cancer cells as a potential therapeutic target. 48,49 Although various drugs have been tested in vivo and in clinical trials to neutralize HSP90B1 in several other cancer types, none has been introduced for breast cancer treatment owing to toxicity-and specificity-related issues.…”
Section: Combinational Treatmentmentioning
confidence: 85%